2010
DOI: 10.1073/pnas.0906087107
|View full text |Cite
|
Sign up to set email alerts
|

Rapid structural alterations of the active zone lead to sustained changes in neurotransmitter release

Abstract: The likelihood with which an action potential elicits neurotransmitter release, the release probability (p r ), is an important component of synaptic strength. Regulatory mechanisms controlling several steps of synaptic vesicle (SV) exocytosis may affect p r , yet their relative importance in determining p r and eliciting temporal changes in neurotransmitter release at individual synapses is largely unknown. We have investigated whether the size of the active zone cytomatrix is a major determinant of p r and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
133
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 37 publications
8
133
1
Order By: Relevance
“…It also corresponds well to the finding that prolonged depolarization leads to a reduction of both N and p vr (Moulder et al, 2004). Moreover, in a recent study, Matz et al (2010) used genetically expressed pHluorin to examine p syn in hippocampal cell cultures. They find that p syn changes spontaneously on a timescale of minutes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It also corresponds well to the finding that prolonged depolarization leads to a reduction of both N and p vr (Moulder et al, 2004). Moreover, in a recent study, Matz et al (2010) used genetically expressed pHluorin to examine p syn in hippocampal cell cultures. They find that p syn changes spontaneously on a timescale of minutes.…”
Section: Discussionmentioning
confidence: 92%
“…However, rapid structural remodeling of synapses has been demonstrated previously. Another recent study at cultured hippocampal neurons found that the amount of fluorescently labeled Bassoon molecules at AZs changes on a timescale of minutes (Matz et al, 2010), suggesting a very dynamic structure of the cytomatrix. Furthermore, at postsynaptic densities, structural remodeling on the timescale of even milliseconds has been shown to influence paired-pulse ratios by diffusional exchange of desensitized and un-desensitized glutamate receptors (Heine et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Correlated bouton size changes might arise because boutons form contacts with postsynaptic cells displaying similar tuning properties (e.g., in the same cortical column), whereas spines along a dendrite likely make synapses with axons exhibiting different firing patterns. At the same time, fluctuations in EPB size could decrease the reliability of synaptic transmission (20), degrading the saliency of output signals. Long-term rather than short-term changes in synaptic weight may be at the basis of memory encoding (41).…”
Section: Increased Rates Of Change In Axonal Bouton Size and Cognitivementioning
confidence: 99%
“…Furthermore, because the size of the active zone correlates with the reliability of synaptic transmission (20), and synaptic vesicles are exchanged at high rates between neighboring EPBs along the axon in an activity-dependent manner (50), it is plausible that a combination of the aforementioned mechanisms could contribute to the increased rate of fluctuations in the size of Ag cortical EPBs (Fig. 5).…”
Section: Increased Rates Of Change In Axonal Bouton Size and Cognitivementioning
confidence: 99%
See 1 more Smart Citation